Quantifying the Nitrogen and Water Stress of Maize Using Spectral Vegetation indices - Ramachandiran, K.; Pazhanivelan, S.; Amanullah, M. Mohamed; Geethalakshmi, V.; Sivasamy, R.; Raja, N. Asoka (International Journal of Bio-resource and Stress Management, 2023)
Numerous spectral vegetation indices have been developed to characterize vegetation canopies. These indices will easily predict or quantify the plant stress at earlier with help of remote sensing techniques. Field experiments were conducted at the Tamil Nadu Agricultural University, Coimbatore, Tamilnadu, India during rabi 2013 with maize crop. To ensure the stressed environment, the crop was subjected to two irrigation levels (CPE: 0.80, 0.50) and five staggered nitrogen levels (0, 50, 75, 100 and 125% of RDN. The experiment was laid out in FRBD with three replication. Measured spectral reflectance curve of maize exhibited a broad low intensity peak centered in the green region at 550 nm and a sharp rise starting at about 685 nm to a plateau in the vicinity of 762 nm under unstressed environment created with irrigation at 0.80 IW/CPE ratio and fertilizer application at 100% RDN. Significant differences in reflectance were established for nitrogen and water stress at green and NIR region. The spectral indices viz., NDVI, GNDVI, RVI, LCI, IR-RED and SR recorded higher value on unstressed maize crop and plants under stress caused reduction in value of these indices at 60 and 90 DAS. All the spectral vegetation indices correlated positively with LAI and SPAD values with a correlation coefficient above 0.80 at both stages. These results highly support the ability of spectral vegetation indices to quantify the combined effect of nitrogen and water stress on maize too earlier through remote sensing.